Engineering liver microtissues to study the fusion of HepG2 with mesenchymal stem cells and invasive potential of fused cells. (30th November 2021) - Lee, Junmin; Ung, Aly; Kim, Hanjun; Lee, KangJu; Cho, Hyun-Jong; Bandaru, Praveen; Ahadian, Samad; Dokmeci, Mehmet R; Khademhosseini, Ali
Abstract: Increasing evidence from cancer cell fusion with different cell types in the tumor microenvironment has suggested a probable mechanism for how metastasis-initiating cells could be generated in tumors. Although human mesenchymal stem cells (hMSCs) have been known as promising candidates to create hybrid cells with cancer cells, the role of hMSCs in fusion with cancer cells is still controversial. Here, we fabricated a liver-on-a-chip platform to monitor the fusion of liver hepatocellular cells (HepG2) with hMSCs and study their invasive potential. We demonstrated that hMSCs might play dual roles in HepG2 spheroids. The analysis of tumor growth with different fractions of hMSCs in HepG2 spheroids revealed hMSCs' role in preventing HepG2 growth and proliferation, while the hMSCs presented in the HepG2 spheroids led to the generation of HepG2-hMSC hybrid cells with much higher invasiveness compared to HepG2. These invasive HepG2-hMSC hybrid cells expressed high levels of markers associated with stemness, proliferation, epithelial to mesenchymal transition, and matrix deposition, which corresponded to the expression of these markers for hMSCs escaping from hMSC spheroids. In addition, these fused cells were responsible for collective invasion following HepG2 by depositing Collagen I and Fibronectin in their surrounding microenvironment. Furthermore, we showed that hepatic stellate cells (HSCs) could also be fused with HepG2, and the HepG2-HSC hybrid cells possessed similar features to those from HepG2-hMSC fusion. This fusion of HepG2 with liver-resident HSCs may propose a new potential mechanism of hepatic cancer metastasis.